Directly Photoexcited Oxides for Photoelectrochemical Water Splitting. Issue 19 (3rd September 2019) - Pan, Linfeng; Vlachopoulos, Nick; Hagfeldt, Anders
Abstract: Artificial photosynthesis promises to become a sustainable way to harvest solar energy and store it in chemical fuels by means of photoelectrochemical (PEC) cells. Although it is intriguing to shift the fossil‐fuel‐based economy to a renewable carbon‐neutral one, which will alleviate environmental problems, there is still a long way to go before it rivals traditional energy sources. Existing solar water‐splitting devices can be sorted into three categories: photovoltaic‐powered electrolysis, PEC water splitting, and photocatalysis (PC). PEC and PC systems hold the potential to further reduce the cost of devices due to their simple structures in which photoabsorbers and catalysts are closely integrated. PC is expected to be the least expensive approach; however, additional costs and concerns are brought about by the subsequent explosive gas separation. At the heart of all devices, semiconductor photoabsorbers should be efficient, robust, and cheap to satisfy the strict requirements on the market. Therefore, this Review intends to give readers an overview on PEC water splitting, with an emphasis on oxide material‐based devices, which hold the potential to support global‐scale production in the future. Abstract : Encouraging break ups : Semiconductor photoelectrochemistry holds great promise for solar energy storage for use as fuels. Through continuous research and development in this area, substantial progress has been achieved in photoelectrochemical water splitting during the last two decades. Herein, essential knowledge and recent achievements in solar water‐splitting research are summarized, with an emphasis on oxide semiconductors.